2019
DOI: 10.4013/sdrj.2019.121.08
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Artificial Intelligence on Design Thinking practice: Insights from the Ecosystem of Startups

Abstract: Design Thinking (DT) is spreading out in the managerial community as an alternative way to innovate products and services respect to the classical stage-gate model mostly linked to technology-push innovative patterns. At the same time few disruptive technologies -like Artificial Intelligence (AI) and machine learning -are impacting the ways companies manage their knowledge and activate innovation and design processes. What is the impact that AI is exerting on DT practices? What are the main changes that DT is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
(19 reference statements)
0
10
0
2
Order By: Relevance
“…(3) Process and praxis design: this stage is to design learning activities that encourage student development by addressing students' needs and interests, and alleviating AI fear through the design of socially meaningful group-based projects. To construct student-centered learning environments, we recommend that teachers should approach the subject area of AI from a design-thinking perspective with positive thinking that gains an empathic understanding of the people to design solutions of the problems [17,33]. This approach supports different types of students to better understand the complex world of AI by ensuring the participation of more students [34].…”
Section: Practical Recommendationsmentioning
confidence: 99%
“…(3) Process and praxis design: this stage is to design learning activities that encourage student development by addressing students' needs and interests, and alleviating AI fear through the design of socially meaningful group-based projects. To construct student-centered learning environments, we recommend that teachers should approach the subject area of AI from a design-thinking perspective with positive thinking that gains an empathic understanding of the people to design solutions of the problems [17,33]. This approach supports different types of students to better understand the complex world of AI by ensuring the participation of more students [34].…”
Section: Practical Recommendationsmentioning
confidence: 99%
“…In their article, Zhu et al [15] revealed that the research phase could be accelerated by including artificial intelligence (AI), e.g. in the form of a digital assistant (DA), which led to shortening of the time dedicated for this activity [21]. While AI in the form of DAs can take over different roles in collaboration (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Despite anecdotes regarding AI threats to design disciplines (Girling, 2016(Girling, , 2017, research on AIbased design is gaining ground. It has already covered topics such as AI's impact on design practices (Cautela et al, 2019;Liao et al, 2020;Verganti et al, 2020) and practitioners' roles in interacting with AI (Angell, 2019;Liu & Nah, 2019). While investigating these complex issues, scholars listened to design practitioners (Main & Grierson, 2020;Pfeiffer, 2018) such as UX designers (Churchill et al, 2018;Dove et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In a so-called 'AI design' context, solutions are delivered through intelligent systems during the design process. Notwithstanding, current approaches are restricted to employment of generative algorithms to support the creative process (L. or apply algorithms to automatise design tasks that used to require intense manipulation (Cautela et al, 2019). Since humans still mediate these processes, AI-empowered design (Verganti et al, 2020) might better describe the contemporary use of AI in the design area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation